Strategic Human Resource Mapping and Sustainable HRM: Balancing Productivity and Employee Well-being - Sugiharto, Bambang; Hiya, Nirmadarningsih; Simamora, Harkim; Gaol, Nickytha Linch De Hans Lumban; Andriani, Maya (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study explores the strategic transformation of Human Resource Management (HRM) in the context of technological advancement, employee-centric practices, and sustainability integration. As HRM evolves from a traditional administrative function to a strategic organizational driver, technologies such as Big Data Analytics (BDA), Artificial Intelligence (AI), and HR Analytics play a critical role in enabling data-driven decision-making. These tools enhance employee attrition prediction, improve person-organization fit, and strengthen employer branding. Simultaneously, Strategic HRM (SHRM) emphasizes the alignment of HR policies with long-term organizational goals, contributing significantly to performance outcomes. Beyond operational efficiency, this paper highlights the growing importance of employee engagement, well-being, and sustainable HRM practices that support a healthy, inclusive, and balanced work environment. Sustainable HRM links employee well-being with organizational productivity while addressing social, environmental, and economic dimensions. The Dynamic Capability Theory provides the theoretical lens to understand how agile HR systems enhance organizational resilience and competitiveness amid rapidly changing business environments. This study formulates twelve hypotheses focusing on four key dimensions: technology integration in HRM, strategic HRM and performance, employee-centric practices, and industry-specific competency challenges. The hypothesized model outlines relationships between independent variables (technology, HRM strategy, competencies), mediating factors (psychological/social aspects, managerial roles), and dependent outcomes (performance, turnover, innovation, commitment). By synthesizing recent literature and identifying theoretical gaps—particularly in the areas of sustainability, social network utilization, and non-R&D employee innovation—this study contributes to advancing HRM research and proposes pathways for future exploration that are inclusive, data-driven, and aligned with dynamic organizational needs.